Teaching geography using Web-GIS to improve students’ spatial thinking ability - Nyokro Mukti Wijaya; Lusi Septiana; Risklarita Simanjuntak; Muhammad Robith Farkhan; Dedy Miswar (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
Web-GIS was a mapping technology that could be used to support the learning process. Although in practice, the use of Web-GIS in learning is still low. Therefore, this study aimed to analyze (1) types of Web-GIS platforms in geography learning, (2) geography topics in Web-GIS-based learning, (3) methods of using Web-GIS in learning, and (4) the impact of Web-GIS on students' spatial thinking ability. The method used was a literature study with content analysis. There were 12 selected articles analyzed from Google Scholar. As a result, (1) the types of Web-GIS platforms that could be used in learning were Arc-GIS online, National Geography MapMaker, Digital Atlas, and Web-GIS INARISK. (2) Geography topics that could be used in Web-GIS-based learning were physical geography, human geography, regional geography, cartography, environment, and disaster. (3) Methods that could be used to use Web-GIS in learning were map investigation, project based learning, blended learning, inquiry, and demonstation. (4) The impact of using Web-GIS was very effective to improve students' spatial thinking ability. From research. Hopefully, in the future there will be more development research on Web-GIS-based media and teaching materials that could be used in geography learning.